Analysis of Tofu Agroindustry in Simpang Tiga Village, Central Kuantan District, Kuantan Singingi Regency - Ilham Akbar; Jamalludin Jamalludin; Haris Susanto (Fakultas Pertanian Universitas Muara Bungo, 2021)
The study was conducted in Simpang Tiga Village, Kuantan Tengah District, Kuantan Singingi Regency. This research is planned for 6 months starting in March 2019 until August 2019. The purpose of this study is to determine the income, R / C value, BEP and Value Added in tofu agro-industry in Simpang Tiga Village, Kuantan Tengah District, Kuantan Singingi Regency. The results of this study were the total average cost of Rp 1,937,434.57 / Production. Admissions obtained an average of Rp. 3,813,333.33 / production with an average net profit of Rp 1,875,898.76 / Production. The average efficiency value of 1.98 means that the tofu agro-industry business has been efficient and profitable. BEP of tofu agroindustry production is 363,27 Kg on average and BEP of tofu agroindustry revenue is Rp. Rp.2.708,02/ Kg. The added value of tofu agroindustry is Rp. 10,066.67 / Kg or 48.40%.